2015
DOI: 10.4049/jimmunol.1500150
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia Inhibits Autophagy and Bacterial Killing in Human Macrophages by Increasing Expression of Bcl-2 and Bcl-xL

Abstract: Hypercapnia, the elevation of CO2 in blood and tissue, commonly develops in patients with advanced lung disease and severe pulmonary infections, and is associated with high mortality. We previously reported that hypercapnia alters expression of host defense genes, inhibits phagocytosis, and increases the mortality of Pseudomonas pneumonia in mice. However, the effect of hypercapnia on autophagy, a conserved process by which cells sequester and degrade proteins and damaged organelles that also plays a key role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 77 publications
8
37
0
Order By: Relevance
“…Consistent with this hypothesis, we and others have shown that hypercapnia inhibits expression of IL-6, TNF and other cytokines important for host defense (15-17). Cummins and colleagues have shown that elevated CO 2 inhibits activation of the canonical NF-κB pathway (18, 19) that drives expression of many host defense genes, while promoting activation of the non-canonical NF-κB component RelB (18, 19), whose function is largely anti-inflammatory and immunosuppressive.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with this hypothesis, we and others have shown that hypercapnia inhibits expression of IL-6, TNF and other cytokines important for host defense (15-17). Cummins and colleagues have shown that elevated CO 2 inhibits activation of the canonical NF-κB pathway (18, 19) that drives expression of many host defense genes, while promoting activation of the non-canonical NF-κB component RelB (18, 19), whose function is largely anti-inflammatory and immunosuppressive.…”
Section: Introductionsupporting
confidence: 85%
“…However, in our in vitro studies, suppression of cytokine gene expression, phagocytosis and autophagy by elevated CO 2 levels was independent of acidosis (15-17). Further, hypercapnia increased the mortality of bacterial pneumonia in mice with acute and chronic hypercapnia to the same degree, despite more severe acidosis in animals with acute hypercapnia compared to chronic hypercapnia (due to renal compensation in the latter group) (16).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…lysosomal degradation of HIF-␣ protein, elevated CO 2 has recently been demonstrated to inhibit macroautophagy in macrophages (44).…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, we have shown that hypercapnia inhibits phagocytosis, autophagy, and bacterial killing in mouse and human macrophages. 9,12 Interestingly, elevated CO 2 has immunosuppressive effects in Drosophila , as well as in mammalian systems. We found that hypercapnia inhibits expression of antimicrobial peptides (AMPs) in Drosophila S2* cells and that it decreases bacterial clearance and increases the mortality of bacterial infections in Drosophila in vivo.…”
Section: Introductionmentioning
confidence: 99%